Answer:
x = 6 months.
The equation is given by $45 + ($49.45 × x) = ($56.95 × x).
Step-by-step explanation:
i) Let x be the number of months of Internet Service purchased till the Fast
Internet charges and Quick Internet charges become the same.
ii) Charges for Fast Internet for x months is given by $45 + ($49.45 × x)
iii) Charges for Quick Internet for x months is given by ($56.95 × x)
iv) According to the first statement we will now equate the equations in ii)
and iii) and solve for x.
Therefore, $45 + ($49.45 × x) = ($56.95 × x)
45 + 49.45 x = 56.95 x
Therefore (56.95 - 49.45) x = 45
7.50 × x = 45
Therefore x = 45 ÷ 7.5 = 6
Y= mx+b
Y= 1x -2
Good luck
Answer:
c
Step-by-step explanation:
start before a and count until you get to B
Answer:
24
Step-by-step explanation:
:)
The absolute value of 14 is 14.l
Hope it helps :)